2013
DOI: 10.1097/dad.0b013e318272c104
|View full text |Cite
|
Sign up to set email alerts
|

Reticulin and NM23 Staining in the Interpretation of Lymph Nodal Nevus Rests

Abstract: Melanocytic nevus rests in lymph nodes are a known diagnostic challenge, especially in patients with a history of melanoma. Reticulin and NM23 have been studied in this context. The pattern of reticulin staining in melanomas surrounds groups/nests of melanocytes but individual cells in benign nevi. NM23, a metastasis-suppressor gene, has an association with metastatic potential in melanomas and some carcinomas. Twenty-eight cases (14 cases of metastatic melanoma to lymph nodes and 14 cases of lymph node nevus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
8
1
2
Order By: Relevance
“…There are rare reports of melanocytic rests presenting within lymph node sinuses or parenchyma, usually with associated cortical or medullary deposits . Recently Kanner et al observed reticulin staining surrounding the individual nodal melanocytes of nodal melanocytic nevi, whereas reticulin staining in metastatic melanoma surrounds groups of cells . In our cases, reticulin stain was not helpful in distinguishing benign from malignant deposits because nodal melanocytes could not be reliably distinguished from other normal nodal structures such as vessels with this staining preparation.…”
Section: Discussioncontrasting
confidence: 57%
“…There are rare reports of melanocytic rests presenting within lymph node sinuses or parenchyma, usually with associated cortical or medullary deposits . Recently Kanner et al observed reticulin staining surrounding the individual nodal melanocytes of nodal melanocytic nevi, whereas reticulin staining in metastatic melanoma surrounds groups of cells . In our cases, reticulin stain was not helpful in distinguishing benign from malignant deposits because nodal melanocytes could not be reliably distinguished from other normal nodal structures such as vessels with this staining preparation.…”
Section: Discussioncontrasting
confidence: 57%
“…[ 1 3 ] Recently, a reticulin immunostain was suggested as a means of distinguishing between nevi and metastatic melanoma in lymph nodes. [ 4 ] In the present study, we observed reticulin immunostaining patterns in malignant melanomas, benign intradermal nevi, and blue nevi. We also evaluated the concordance in evaluation of the pattern between observers.…”
Section: Introductionsupporting
confidence: 64%
“…The mean age of patients with nodal nevi is around 53 years (range: 2‐84 years) 1‐3,5‐30 . Nodal nevi are most often found in SLN of melanoma and breast cancer patients; thus, they are more likely to be observed in axillary and inguinal lymph nodes 1‐3,5‐31 . In breast cancer patients, nodal nevi occur almost entirely in females.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reticulin tends to be around groups of tumor cells (5-10 cells). On the contrary, in nodal nevi, the reticulin staining is more likely to be localized to individual nevus cells 26. Recently, Vysis melanoma FISH probes targeting 6p25 (RREB1), 6q23 (MYB), 11q13 (CCND1), and CEP6 have been widely used in differential diagnosis of nevi and malignant melanomas 35.…”
mentioning
confidence: 99%